Analisa Peranan dan Pemanfaatan Teknologi dalam Pembelajaran di Era Pandemi - Salsabila, Unik; Nabila, Jihan; Tasnim, Itsna Hilya; Aini, Whulan Khinanti Nur (TSAQOFAH, 2022)
The purpose of this study was to determine the role of educational technology in internalizing Islamic Religious Education in schools. The method used by the writer in this research is qualitative research with interview approach and literature study. The results showed that the role of technology is needed during a pandemic to become an intermediary or means of communication between teachers, students and parents. With technology, it can simplify the learning process without having to meet face to face. The delivery of material can be given through the platform used for learning, such as one of the firsttier schools in Batur Banjarnegara using the WhatsApp platform, google meet, google classroom, zoom cloud meeting and other platforms.